Factors that affect work life balance among women employees at Johor Corporation / Madihah Mat Rani and Muhammad Syafiq Rushdan - Mat Rani, Madihah; Rushdan, Muhammad Syafiq (Faculty of Business and Management, 2016)
In recent years, work life balance is one of the important and challenging issues being faced by the women employees. Work life balance can be refers as maintaining the balance between performing roles and responsibilities at home and at work. Work life balance need more attention due to the reason that an individual’s work life and personal may be conflict to one another. Therefore, this study was conducted with three main objectives in order to achieve the purpose of this research which first objective is to identify the level of social support, reward and recognition, flexible working hours, and work-life balance among women employees in Johor Corporation. Next objective is to determine the relationship between social support, reward and recognition, flexible working hours, and work life balance among women employees in Johor Corporation. Third objective is to investigate the dominant factors that influence work-life balance among women employees in Johor Corporation. In order to achieve all of the objective, the quantitative research methods were used and the data were gathered by distributing 200 structured questionnaires to all women employees at Johor Corporation. The data were analyzed by using Descriptive Analysis, Pearson Correlation Analysis, and Regression Analysis. The result revealed that there is a significant strong relationship between all factors that affect work life balance among women employees. However, the result highlighted that social support is the most dominant factors that affect work-life balance among women employees, followed by flexible working hours, and reward and recognition. In conclusion, it shows organizations should acknowledge women employees by providing more appropriate work-life balance measures for them.